1993
DOI: 10.4039/ent125161-1
|View full text |Cite
|
Sign up to set email alerts
|

APHANOGMUS FULMEKI ASHMEAD (HYMENOPTERA: CERAPHRONIDAE), A PARASITOID OF APHIDOLETES APHIDIMYZA RONDANI (DIPTERA: CECIDOMYIIDAE)

Abstract: The predatory gall midge, Aphidoletes aphidimyza (Rondani 1847), is a biological control agent used worldwide to control aphids. Mass-production methods are well established in Canada, the Netherlands, England, Germany, Finland, and the former U.S.S.R. (cf. van Leiburg and Ramakers 1984). In early March 1991, after 6 years of massproduction of A. aphidimyza on a rapidly increasing scale, two minute adult hymenopterous parasitoids were observed eclosing from a sample of pupae at a commercial insectary in Britis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Four species of parasitoid wasps have been recorded attacking A. aphidimyza : Synopeas rhanis , Aphanogmus fulmeki , Gastrancistrus sp. and an unidentified braconid species . Parasitoids are more of a concern as contamination in the mass‐rearing of A. aphidimyza , where they might reduce the efficiency of the rearing, rather than in the greenhouse or field.…”
Section: Aphidoletes Aphidimyza As Biocontrol Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…Four species of parasitoid wasps have been recorded attacking A. aphidimyza : Synopeas rhanis , Aphanogmus fulmeki , Gastrancistrus sp. and an unidentified braconid species . Parasitoids are more of a concern as contamination in the mass‐rearing of A. aphidimyza , where they might reduce the efficiency of the rearing, rather than in the greenhouse or field.…”
Section: Aphidoletes Aphidimyza As Biocontrol Agentmentioning
confidence: 99%
“…and an unidentified braconid species. 107 Parasitoids are more of a concern as contamination in the mass-rearing of A. aphidimyza, where they might reduce the efficiency of the rearing, rather than in the greenhouse or field. However, the presence of the parasitoids of A. aphidimyza in the crop may be underestimated due to the difficulty of detecting parasitism in a commercial field.…”
Section: Intraguild Predation and Interspecific Competitionmentioning
confidence: 99%
“…Body size polyphenism is usually induced by variability in host body size in polyphagous and brood size in gregarious parasitoid Hymenoptera (Quicke, 1997; Nalepa & Grisell, 1993; Medal & Smith, 2015). Numerous ceraphronoid species are known to parasitize hosts with variable body size (Fergusson, 1980; Gilkeson, McLean & Dessart, 1993) and gregariousness is not uncommon (Cooper & Dessart, 1975; Starý, 1977; Liebscher, 1972; Mackauer & Chow, 2015; Takada, 1973). Mackauer & Chow (2015) A clear relationship between ceraphronoid body mass and brood size was recently shown in the facultatively gregarious Dendrocerus carpenteri (Curtis, 1829), where the body mass of a single solitary specimen did not differ from the combined body mass of two gregarious specimens Mackauer & Chow (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar intraspecific variability is common among microhymenoptera and can be stimulated by alternative host species with different nutritional quality (Nalepa & Grisell, 1993; Medal & Smith, 2015) gregariousness with variable brood sizes (Harvey et al, 1998), and climatic differences, such as temperature (Wu et al, 2011). Ceraphronoids are parasitoids on insect parasitoid and predator larvae (Haviland, 1920; Withycombe, 1924; Kamal, 1939) and have a broad host range (Gilkeson, McLean & Dessart, 1993; Sullivan & Völkl, 1999). Dendrocerus carpenteri , for example, has been reared from >70 aphidiine (Braconidae) species (Fergusson, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary identification revealed that the ceraphronid was a member of Aphanogmus Thomson (Hymenoptera: Ceraphronidae), which contains at least 100 species worldwide (Johnson and Musetti 2004, Evans et al 2005, Buhl et al 2010). About 20% of them have been known as parasitoids of various insects including Cecidomyiidae (Diptera), Bethylidae, Ichneumonidae (Hymenoptera) and Cybocephalidae (Coleoptera) (Oatman 1985, Gilkeson et al 1993, Polaszek and Dessart 1996, Evans et al 2005). Host information for the remaining 80% has not been provided.…”
Section: Introductionmentioning
confidence: 99%